Effects of acupuncture on the outcome of tinnitus: An overview of systematic reviews - Xu, Xianpeng; Xie, Hui; Liu, Zifeng; Guo, Tao; Zhang, Ying (Frontiers in Neurology, 2022)
Background To systematically summarize the evidence for the efficacy of acupuncture in tinnitus treatment, we assessed the methodological quality, reporting quality, and evidence quality of systematic reviews/meta-analyses (SRs/MAs) of acupuncture in the treatment of tinnitus. Methods From inception to March 2022, we conducted a detailed and comprehensive search of eight electronic databases in Chinese and English. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2), the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) were used to assess methodological quality, reporting quality and evidence quality for inclusion in SRs/MAs, respectively. Results Fourteen published SRs/MAs met the inclusion criteria and were included in the study. Eleven studies reported that acupuncture was effective in treating tinnitus, and three studies reported that no firm conclusions could be drawn about the effectiveness of acupuncture in treating tinnitus. The results of the AMSTAR-2 assessment showed that the methodological quality of the included studies was relatively low in general, with one being moderate quality and the rest being very low quality. The PRISMA checklist evaluation results showed that no studies fully report checklists, with protocol registration and search strategies being the main reporting weaknesses. The GRADE assessment showed that no results were high-quality evidence, 17 results were moderate-quality evidence, 25 results were low-quality evidence, and 12 results were very low-quality evidence. Conclusion Acupuncture seems to be a positive and effective treatment for tinnitus. However, the methodological quality and quality of evidence for SRs/MAs in the included studies were generally low, and this result must be viewed with caution. Therefore, more high-quality, large-scale, multi-center randomized controlled trials are needed in the future to verify the effectiveness of acupuncture in the treatment of tinnitus.